Multiparametric Ultrasound (MPUS) Imaging: Terminology Describing the Many Aspects of Ultrasonography - Sidhu, P. S. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Magnetic Resonance (MR) imaging has, for a number of years, enjoyed the adulation of many in the medical profession, providing a unique and often invaluable insight into the human body, especially in the areas of neuroimaging and musculoskeletal assessment. Numerous MR sequences and types of imaging have been developed, with functional imaging playing an important role in diagnosis. The many different aspects of MR imaging presents an accolade richly deserved by all working in the field of MR imaging. Language often used to describe the multitude of imaging techniques of MR is the term ‘multiparametric’. This gives the impression of multiple techniques, all contributing in a unique manner to aid the interpretation of an abnormality, giving an air of comprehensiveness in the pursuit of the final goal. This establishes MR imaging at the forefront of advances achieved in imaging and medicine. Consequently the impression of MR imaging is that of the ‘bedrock’ of modern technology related to imaging the human body. Furthermore, Computed Tomography (CT) imaging has revolutionised chest imaging, trauma management and plays a substantial role in the assessment of the acute abdomen. There is less scope to lump together different CT techniques under one ‘umbrella’ term, but CT could also use the term ‘multiparametric’ incorporating functional imaging, 3-D reconstruction and imaging in different phase of contrast administration. Ultrasound imaging techniques are often side-lined. Notwithstanding the undoubted strengths of MR and CT imaging, limitations abound; radiation, claustrophobia, sedation in paediatric imaging, expense, availability, and patient movement with, contrast agents implicated in acute and serious long term morbidity.How does ultrasonography (US) fit into this imaging pattern? Viewed as the ‘lowly relation’ of imaging, nonetheless. US is dynamic, patient friendly (the operator can talk to the patient whilst performing the examination!), readily available, repeatable, portable but still perceived to be an inferior imaging technique when contemplated by medical practitioners outside the realm of the enthusiastic US practitioner. Those who use US regularly know this to be untrue; the multifaceted nature of the technique allows considerable versatility and most importantly, is used with no harm to the patient. With adequate training, diagnostic and interventional procedures are conducted with ease and with considerable accuracy. Many new developments in US techniques have enabled additional information from the US examination with little extra effort from the practitioner. The most important additions in recent years have been contrast-enhanced ultrasound (CEUS) and elastography both strain and shear wave elastography. This combined with established B-mode US, colour and spectral Doppler US, 3-D and 4-D imaging allows the term ‘multiparametric ultrasound’ (MPUS) to be added to the terminology used to describe imaging in ultrasonography, perhaps similar to the terminology used in MR imaging. Little extra-effort is needed to add these different US facets to the examination procedure; CEUS giving dynamic functional imaging in many areas including liver lesion characterisation 12, tumour perfusion response to therapy 3 and the presence or absence of vascularity being a crucial aspect of the examination. Elastography, a measure of tissue stiffness, is particularly useful in the liver and in the assessment of focal lesions in superficial structures where strain elastography performs best 45.Ultrasonography practitioners should embrace the term MPUS to describe the multiple facets of the US examination that are taken for granted, allowing a better perception of skills associated with US, in this manner the medical profession will be alerted to the capabilities of an US examination, not just inexpensive but highly informative, diagnostic and with a wealth of useful measurements. Of course MPUS works best were US is established; the liver, kidney, superficial structures (testis, thyroid, lymph nodes) vessels (carotid plaque), gynaecology to name but a few.The testis is one area were the term MPUS has been used in the description of the assessment of focal intra-testicular tumours by a number of authors and aids the interpretation of disease in an area notably successful for US, allowing a more precise and confident diagnosis 6789. Other imaging techniques are not as useful in this area although MR imaging has potential in functional assessment, resolution of MR imaging is inferior to US 10. In this issue it is reported that shear wave elastography may be superior to grayscale for the assessment of carotid plaque vulnerability 11, which if combined with CEUS of carotid plaque, previously investigated 12, would be invaluable in a ‘one-stop’ MPUS examination procedure with addition of the more traditional US criteria for the assessment of stenosis 1314. The use of shear wave elastography is also reported in the assessment of soft tissue tumours 15 which can easily be combined with CEUS to assess vascularity and response to treatment, akin to the assessment of vascular liver tumor response to therapy 16. The use of MPUS in the evaluation of liver disease is well established, CEUS for focal liver lesions is an accurate technique, surpassing assessment with CT and MR imaging in some instances 17. Shear wave elastography is now a main stream investigation in chronic liver disease 1819.Practitioners of US need to embellish the capabilities of the technique, educating colleagues in the medical profession regarding the ever evolving capabilities of US and the accurate role in diagnosis. It may appear to be presumptuous to use ‘multiparametric’ when describing the practice of US but it describes exactly what is occurring; multiple different techniques of US combining to achieve the diagnosis. Most importantly this is accomplished at lower cost and patient morbidity than any other imaging modality. The continuation of an important aspect of medical practice, the physician-patient interaction, will persist and be embellished 20. We should be encouraged to engage with the term MPUS when describing multiple US technique.